THE USE OF ENGLISH COMIC BOOK SERIES IN TEACHING READING COMPREHENSION - Winda Apriani; Machdalena Vianty; Bambang A. Loeneto (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The objectives of this study were to find out whether or not the use of English Comic Book series could improve reading comprehension of the seventh grade students of SMP Negeri 32 Palembang. In this study, one group pre-test and post-test control group design was applied. The population was 170 seventh grade students in academic year 2013/2014. Purposive sampling method was applied and class VII.1 (N=34) and class VII.2 (N=34) were involved as the sample. The data were analyzed by using t-test. The result of the data analysis showed that the mean difference of the pre test and post test of the experimental group was significant (p < 0.05). The result of the independent sample t-test also showed that the mean differences of the post test of experimental group and control group were significant (p < 0.05). These results confirmed that the use of English Comic book series could be used as a reading material to help the seven graders of SMP Negeri 32 improve their reading comprehension. In addition, the result of this study showed that using a variety of reading materials in teaching reading comprehension is important. Key words: reading comprehension, English Comic book series